Sphingolipids in thyroid eye disease - Gulbins, Anne; Görtz, Gina-Eva; Gulbins, Erich; Eckstein, Anja (Frontiers in Endocrinology, 2023)
Graves’ disease (GD) is caused by an autoimmune formation of autoantibodies and autoreactive T-cells against the thyroid stimulating hormone receptor (TSHR). The autoimmune reaction does not only lead to overstimulation of the thyroid gland, but very often also to an immune reaction against antigens within the orbital tissue leading to thyroid eye disease, which is characterized by activation of orbital fibroblasts, orbital generation of adipocytes and myofibroblasts and increased hyaluronan production in the orbit. Thyroid eye disease is the most common extra-thyroidal manifestation of the autoimmune Graves’ disease. Several studies indicate an important role of sphingolipids, in particular the acid sphingomyelinase/ceramide system and sphingosine 1-phosphate in thyroid eye disease. Here, we discuss how the biophysical properties of sphingolipids contribute to cell signaling, in particular in the context of thyroid eye disease. We further review the role of the acid sphingomyelinase/ceramide system in autoimmune diseases and its function in T lymphocytes to provide some novel hypotheses for the pathogenesis of thyroid eye disease and potentially allowing the development of novel treatments.